Analysis of the Need for Digital Teaching Materials Based on Meaningful Learning in Elementary Schools - Ida Ayu Komang Tri Widia Utami; Kadek Hengki Primayana; I Nyoman Pancaria (Walada: Journal of Primary Education, 2026)
This research is motivated by the importance of implementing meaningful Natural and Social Sciences learning in accordance with the demands of the Independent Curriculum, but the availability of teaching materials capable of encouraging active student engagement is still limited. This study aims to analyze the need to develop digital teaching materials based on meaningful learning in elementary schools. The study used a qualitative descriptive approach with data collection techniques in the form of observations and in-depth interviews with fourth-grade teachers in Cluster IV, Banjar District. The results show that Natural and Social Sciences learning has led to student engagement through exploratory activities. However, learning practices are still dominated by the use of textbooks and lecture methods, and the use of interactive digital teaching materials that can visualize concepts and relate material to students' real-life experiences is not optimal. This condition results in low learning interest and suboptimal student conceptual understanding. The implications of this research indicate that the development of digital teaching materials based on meaningful learning is a crucial need to improve the quality of Natural and Social Sciences learning, particularly in creating interactive, contextual, and meaningful learning experiences.